Construction of red-emitting iminocoumarin-based fluorescent borate complexes with a large Stokes shift. (February 2020) - Ren, Xiaojie; Guo, Man; Gong, Junyi; Zhang, Yun; Yang, Lei; Liu, Xingjiang; Song, Xiangzhi
Abstract: Tetra-hydro-quinoxaline (THQ) moiety was used as the electron donor in the construction of a series of red-emitting iminocoumarin-based borate dyes with good fluorescent quantum yields, large Stokes shifts and long-wavelength emissions. These dyes could stain cells and image zebrafish with good performance. Graphical abstract: Image 1 Highlights: A series of new fluorescent borate complexes with enhanced ICT process. Red/NIR emissions (up to 650 nm in DMSO) and large Stokes shift (up to 122 nm in DMSO). Good fluorescent quantum yields (0.65-0.84 in DCM) and large absorption molecular extinction coefficients (104 M-1cm-1). Red/NIR solid fluorescence. Potential application for bioimaging in cells and zebrafish.